Strategies for aggregating risk information in a societal safety context. (May 2022) - Hassel, Henrik; Cedergren, Alexander; Tehler, Henrik
Highlights: The conceptual basis for risk aggregation in societal safety is further developed. Six strategies for aggregating risk information are suggested and formalized. Preconditions for using each aggregation strategy are presented. General challenges are described aiming to facilitate practical applications. Abstract: Risk assessment is a useful tool to inform decision-making when it comes to ensuring the continuous operation of critical societal functions. It can be used on many levels within an organization or on multiple societal levels. One way to conduct risk assessments on a higher system level, such as on national level, is to aggregate risk information from lower-level assessments, e.g. from the regional level. However, the process of aggregating risk information can be highly complex and different strategies for such aggregation are suitable depending on the underlying risk information, the characteristics of the risks that this information represents, and the analysts' intentions in the aggregation process. To use a particular aggregation strategy, different conditions must be met. In addition, throughout the aggregation process, a range of both generic and strategy-specific challenges require attention and careful consideration. Little previous research has focused on describing and systematizing different aggregation strategies, including description of the conditions and challenges for employing the strategies. Therefore, the aim of this paper is to further develop the conceptual basis of aggregation and to propose a set of common aggregation strategies that can be used within the area of societal safety. Furthermore, the paper also aims at describing the conditions and challenges of employing the strategies. In total, six strategies are proposed based on what risk information that needs to be aggregated (likelihoods, consequences or neither). In addition, the aggregation can be simple, in cases where a set of conditions are met, or more complex where overlaps and interactions between scenarios must be considered. The framework can be used to inform the process of aggregating risk information and has relevance across a range of different application areas.